Pengaruh Media Pembelajran terhadap Prestasi Belajar Setingkat Menengah Pertama: Penelitian - Eli Masnawati; Nur Sa’adatut Daraini; Miftakhul Jannah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Learning media includes various tools and sources of information that function to support the learning process. Choosing the right learning media can affect the way students understand information, so it has the potential to develop students' learning achievement. This research serves to examine the effect of learning media on student learning achievement at the junior high school level. This research was examined using a literature study approach with quantitative methods, which involved reviewing accurate academic information. The results of the study show that learning media as teaching materials have a significant impact on improving students' learning achievement. Creative and interactive learning media can foster students' desire and contribution during learning activities, thus having a positive impact on academic outcomes. This study found that the use of learning media is proven to be effective in realizing more powerful and useful knowledge. The use of learning media in this study can be used as an effective plan to improve the quality of education through student learning achievement at the junior high school level.